(untitled) (Bangladesh Critical Care Journal, 2022)
Ascites is an infrequent presentation of poorly controlled congestive cardiac failure. Tense ascites due to heart failure is more infrequent. Whenever there is tense ascites, intra-abdominal hypertension should always be considered. The most deleterious effect of intra-abdominal hypertension is abdominal compartment syndrome. It is a condition that is frequently overlooked and underdiagnosed. Abdominal compartment syndrome is a medical as well as surgical emergency which should be promptly diagnosed and adequately managed; otherwise, it may lead to multiple organ failure and death. Here we present a patient with congestive cardiac failure leading to huge ascites, intra-abdominal hypertension and abdominal compartment syndrome. Bangladesh Crit Care J September 2022; 10(2): 149-153